-37=-3(1+6m)-2(m+7)

Simple and best practice solution for -37=-3(1+6m)-2(m+7) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -37=-3(1+6m)-2(m+7) equation:


Simplifying
-37 = -3(1 + 6m) + -2(m + 7)
-37 = (1 * -3 + 6m * -3) + -2(m + 7)
-37 = (-3 + -18m) + -2(m + 7)

Reorder the terms:
-37 = -3 + -18m + -2(7 + m)
-37 = -3 + -18m + (7 * -2 + m * -2)
-37 = -3 + -18m + (-14 + -2m)

Reorder the terms:
-37 = -3 + -14 + -18m + -2m

Combine like terms: -3 + -14 = -17
-37 = -17 + -18m + -2m

Combine like terms: -18m + -2m = -20m
-37 = -17 + -20m

Solving
-37 = -17 + -20m

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '20m' to each side of the equation.
-37 + 20m = -17 + -20m + 20m

Combine like terms: -20m + 20m = 0
-37 + 20m = -17 + 0
-37 + 20m = -17

Add '37' to each side of the equation.
-37 + 37 + 20m = -17 + 37

Combine like terms: -37 + 37 = 0
0 + 20m = -17 + 37
20m = -17 + 37

Combine like terms: -17 + 37 = 20
20m = 20

Divide each side by '20'.
m = 1

Simplifying
m = 1

See similar equations:

| 3m^3-15m^2+75m=0 | | x^2+y^2-22x+112=0 | | 2b-5b=-9 | | (2x-1)/4+(3x+4)/8=(1-4x)/12 | | 3(z+3)=2(z+8) | | 31=5x+5x-9 | | 9-ln(4-x)=0 | | 4x=-5+2x+18 | | -2(-9w+1)-2w=2(w-1)-2 | | 2x+13=5x-14 | | 5y=2(y+6) | | -5w+3(w-5)=-13 | | 3*2-y=9 | | 3*3-y=9 | | 4x=8+3x | | 2b^4+8b^3+8b^2=0 | | 5+4D=47 | | 6(6v+5)=1+6v | | 7x+6=9x+x | | 250+.10y=350 | | x^2+y^2+30x-2y+210=0 | | 8.5X=11 | | x+.10y=350 | | 600+600= | | 5(x+5)=-5(2x-3)+x | | 23+6y-15=62 | | 5y=x+19 | | 189s=99+10 | | 7x-18=9x+4 | | 5(y-2)=-5y+40 | | 10x=4y+16 | | -c^2-5c+66= |

Equations solver categories